Suscetibilidade a movimentos de massas gravitacionais no município de São Paulo – SP utilizando ferramentas de geoprocessamento - Anjos, Caroline Silva dos [UNIFESP] (2023)
The intensification of urbanization and disorderly occupation in regions of geological and geomorphological instability create areas of significant risk for social and economic losses due to natural disasters caused by gravitational mass movements. In this context, there is a clear need to map areas susceptible to these movements as an essential tool for land use management and urban planning In this study, the main objective is to draw up a map of susceptibility to gravitational mass movements in the municipality of São Paulo (SP) through the application of geoprocessing techniques, using free geological and remote sensing data. The methodology adopted included the qualitative combination of thematic maps and the classification of conditioning factors, such as Declivity, Lithology, Land Use, Vertical Curvature and Lineament Density. This process was followed by data cross-checking and validation of the final map. The results show that Low (41,78%) and Moderate (46,42%) susceptibility areas predominate in the territory as a whole. However, the Moderate and High classifications (11,79%) predominantly occupy the edges of the municipality, while the Low class predominate in the central region of São Paulo.